GLOBECOM 2020 - 2020 IEEE Global Communications Conference 2020
DOI: 10.1109/globecom42002.2020.9322303
|View full text |Cite
|
Sign up to set email alerts
|

Keep the bursts and ditch the interleavers

Abstract: To facilitate applications in IoT, 5G, and beyond, there is an engineering need to enable high-rate, low-latency communications. Errors in physical channels typically arrive in clumps, but most decoders are designed assuming that channels are memoryless. As a result, communication networks rely on interleaving over tens of thousands of bits so that channel conditions match decoder assumptions. Even for short high rate codes, awaiting sufficient data to interleave at the sender and de-interleave at the receiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…When permutation exhausts, an extra nonflipped bit is included and the permutation process restarts. This pattern generator gives the decoder some advantages with burst errors (specifically treated in [28]) and the resulted algorithm is named as GRAND with simple order sweeping (GRAND-SOS).…”
Section: Guessing Random Additive Noise Decoding a Grand-sos For Hard...mentioning
confidence: 99%
See 1 more Smart Citation
“…When permutation exhausts, an extra nonflipped bit is included and the permutation process restarts. This pattern generator gives the decoder some advantages with burst errors (specifically treated in [28]) and the resulted algorithm is named as GRAND with simple order sweeping (GRAND-SOS).…”
Section: Guessing Random Additive Noise Decoding a Grand-sos For Hard...mentioning
confidence: 99%
“…GRAND's universality stems from its effort to identify the effect of the noise, from which the code-word is deduced. Originally introduced as a hard detection decoder [26]- [28], a series of soft detection variants, SRGRAND [29], [30], ORBGRAND [31] and SGRAND [32], have since been proposed that make distinct quantization assumptions. Both hard and soft detection versions of GRAND are ML decoders.…”
Section: Introductionmentioning
confidence: 99%
“…Coded packets are transmitted after the entire interleaving block, which is multiple times greater than the generation size. The authors of [30] showed that replacing interleaving techniques with RLC at the link layer can reduce latency, despite losing the ability to recover burst losses.…”
Section: Coding Variants and Characteristicsmentioning
confidence: 99%
“…The theoretical foundations and properties of GRAND were laid in [3] and [4]. A practical implementation of the GRAND framework, referred to as GRAND Markov order (GRAND-MO), was presented in [5]. GRAND-MO is a hard detection decoder of binary codewords that have been impaired by errors correlated over time.…”
Section: Introductionmentioning
confidence: 99%